Facing the Digital Era: CBT-Assisted HOTS Questions Experiment To Improve Digital Literacy Capability - Romawanti, Istri; Mudiono, Alif; Suciptaningsih, Oktaviani Adhi (Jurnal Ilmiah Iqra', 2024)
The challenges of the ever-growing digital world require students to have digital literacy skills. However, this ability is not yet fully possessed by students, especially at the Elementary School/Madrasah Ibtidaiyah level. Therefore, efforts are needed to improve digital literacy skills at the Elementary School/Madrasah Ibtidaiyah level. This research aims to find out whether giving HOTS questions based on CBT can improve students' digital literacy skills at MI Perwanida, Blitar City. The type of research used is quasi-experimental research or quasi-experiment with a pretest-posttest control group design. The population in this study were all class IV students at MI Perwanida, Blitar City. Samples were taken using a side random technique. Data collection techniques used questionnaires and tests, then analyzed using the independent t-test. Based on the research results, it shows that the experimental class that was taught using HOTS questions assisted by CBT had good digital literacy skills compared to the control class.